2017
DOI: 10.1021/acsbiomaterials.7b00575
|View full text |Cite
|
Sign up to set email alerts
|

Dispersible MoS2 Nanosheets Activated TGF-β/Smad Pathway and Perturbed the Metabolome of Human Dermal Fibroblasts

Abstract: In postgraphene two-dimensional materials (2DMs), MoS2 has attracted increasing attention in the biomedical field due to its excellent physicochemical properties. However, the toxicity and biocompatibility evaluation of MoS2 is not fully addressed. Herein, chitosan functionalized MoS2 (CS-MoS2) nanosheets, which showed perfect dispersibility and stability performances, were synthesized and characterized. We found that CS-MoS2 nanosheets inhibited the viability of human dermal fibroblasts (HDFs) moderately whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Actually, whether MSN exposure induces ROS production is still a controversial topic. Yu et al demonstrated that chitosan functionalized MSNs induced ROS accumulation in human dermal cells 37 and in the gills and liver of adult zebrafish. 38 Consistently, Pardo et al 39 found that fullerene-like MSNs could induce robust protective antioxidant/detoxification defenses in human bronchial cells, indicating ROS generation in this cell line.…”
Section: Ros-induced Cytoskeleton Arrangement Participates In the Impmentioning
confidence: 99%
“…Actually, whether MSN exposure induces ROS production is still a controversial topic. Yu et al demonstrated that chitosan functionalized MSNs induced ROS accumulation in human dermal cells 37 and in the gills and liver of adult zebrafish. 38 Consistently, Pardo et al 39 found that fullerene-like MSNs could induce robust protective antioxidant/detoxification defenses in human bronchial cells, indicating ROS generation in this cell line.…”
Section: Ros-induced Cytoskeleton Arrangement Participates In the Impmentioning
confidence: 99%
“…However, the interaction between 2D TMDCs and cells certainly will disturb cell homeostasis. Further biosafety evaluation indicated that 2D TMDCs affected cell behaviors, such as cell proliferation, differentiation (Zou et al, 2017), cell adhesion, spreading (Suhito et al, 2017), oxidative stress (Yang et al, 2014), cell metabolism (Yu Y. et al, 2017), and cell autophagy . Singlelayer MoS 2 nanosheets promoted proliferation and accelerated myogenic differentiation in human embryonic lung fibroblasts (HELFs).…”
Section: Biosafety Evaluation Of 2d Tmdcsmentioning
confidence: 99%
“…High levels of oxidative stress induced by single-layer MoS 2 nanosheets caused disturbance to Akt related signaling pathway (Zou et al, 2017) and enhanced antibacterial activity (Yang et al, 2014). In addition, chitosan functionalized MoS 2 nanosheets activated TGF-β/Smad pathway and disturbed cellular metabolic process through interacting with EGFR on human dermal fibroblasts cells surface (Yu Y. et al, 2017). WS 2 nanosheets induced obvious alterations in metabolic pathways and metabolites and the phase composition made a difference on metabolomics in algae (Yuan et al, 2018).…”
Section: Biosafety Evaluation Of 2d Tmdcsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TMDs could potentially be risky to human health and the environment (Guiney et al, 2015, 2018; Kumar et al, 2017). For example, MoS 2 has been shown to be toxic toward planktonic cells, biofilms, and mammalian cells in the presence of electron donors (Fan et al, 2015), to bind to the K + channels and disturb their functions (Gu et al, 2018), to activate TGF-beta/Smad pathways and perturb the metabolome of human dermal fibroblasts (Yu et al, 2017), and to exhibit cytotoxicity and impact inflammation (Moore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%